Atypical Bilateral Acute Iris Transillumination: A Case Report - Ying Hu; Yuan Xie; Mugen Liu; Junyu Fan; Yang Zhang; Chunyan Qiao (Case Reports in Ophthalmology)
Introduction: Bilateral acute iris transillumination (BAIT) is characterized by acute bilateral onset of intense pigment dispersion in the anterior chamber, diffuse iris transillumination, and mydriatic atonic pupils, accentuated pigment deposition in the angle of anterior chamber, and elevated intraocular pressure (IOP). Herein, we report an unusual case of a Chinese patient with BAIT presented to our hospital with no iris transillumination defect. Case Presentation: A 37-year-old male patient presented to our settings with bilateral photophobia, redness, and blurry vision. The symptoms began acutely following a respiratory illness, for which he was treated with moxifloxacin. The patient demonstrated a profound thick layer of pigment deposition on the anterior surface of the lens, corneal endothelial pigment dusting, and trabecular meshwork hyperpigmentation. He was previously diagnosed with acute anterior uveitis with accentuated IOP rise, and was subsequently treated with topical corticosteroids, cycloplegic, and IOP-lowering medications. Despite aggressive medical treatment, IOP remained refractory. The retinal nerve fiber layer severely restricted in both eyes (OU). He was then referred to our glaucoma consultant practice. Although low-energy Selective Laser Trabeculoplasty (SLT) (Quantel, USA) was then performed, it elicited no favorable response, a result that was different compared to previous reports on Caucasian patients. Finally, we performed binocular trabeculectomy combined with mitomycin application, resulting in the optimal IOP control. Conclusion: BAIT in Chinese patients has atypical characteristics, which can highly contribute to misdiagnosis and therapeutic delay with significant consequences. Simultaneously, it is essential to differentiate BAIT from iridocyclitis and pigment dispersion syndrome.